An Implementation of Problem-Based Learning Model through Flipped Classroom Sevima Edlink Application to Improve Students' Critical Thinking Skills - Ferdiansyah, Arbi; Maryuningsih, Yuyun; Juanda, Anda; Lengkana, Dewi (Biosfer: Jurnal Tadris Biologi, 2025)
This study aims to apply the application through Flipped Classroom learning media assisted by Sevima Edlink application in improving students' critical thinking skills on excretory system material in class XI Senior High School. This study used a quantitative method with a quasi-experimental design using a pretest-posttest control group design. Data analysis showed a significant difference in improving critical thinking skills. The experimental group got an average score of 0.60 (Medium) while the control group got an average score of 0.24 (Low), which was shown by the results of the N-Gain and t-test statistical tests. Thus, the application of PBL (Problem Based Learning) model through Flipped Classroom assisted by Sevima Edlink can be an effective alternative in improving students' critical thinking skills, especially in learning biology. Penerapan Model Pembelajaran Pbl (Problem Based Learning) Melalui Flipped Classroom Berbantuan Sevima Edlink Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa ABSTRAK Penelitian ini bertujuan untuk menerapkan penerapan melalui media pembelajaran Flipped Classroom berbantuan aplikasi Sevima Edlink dalam meningkatkan keterampilan berpikir kritis siswa pada materi sistem ekskresi di kelas XI SMA. Penelitian ini menggunakan metode kuantitatif dengan desain quasi-experimental menggunakan pretest-posttest control group design. Analisis data menunjukkan adanya perbedaan yang signifikan dalam peningkatan keterampilan berpikir kritis. kelompok eksperimen mendapat rata-rata nilai 0.60 (Sedang) sedangkan kelompok kontrol mendapat rata rata nilai 0.24 (Rendah), yang ditunjukkan oleh hasil uji statistik N-Gain dan t-test. Dengan demikian, penerapan model PBL (Problem Based Learning) melalui Flipped Classroom berbantuan Sevima Edlink dapat menjadi alternatif yang efektif dalam meningkatkan keterampilan berpikir kritis siswa, khususnya dalam pembelajaran biologi.